Experience with Pediatric Chronic Immune Thrombocytopenia over 30 Years in the Era before Eltrombopag - Begum S. Koc; Gul Nihal Ozdemir; Javid Alakbarli; Hilmi Apak; Tiraje Celkan (MDPI AG, 2024)
Background: There is limited information on the natural course of chronic ITP in children. We aimed to evaluate the clinical and demographic characteristics of children with chronic ITP in the era before the availability of eltrombopag. Methods: A total of 86 children with chronic ITP between 1978-2014 were included. Demographic findings, laboratory results, clinical signs, bleeding scores, response time and time of complete remission were recorded. Results: The male/female ratio was 1.09, and median follow-up time was 3 years (range: 1.5-17 years). The median age at diagnosis of chronic ITP was 7 years (range: 2-17), and the median initial platelet count was 10 × 109/L (range: 1-66 × 109/L). Petechiae/ecchymoses were the most common clinical sign (86%) and followed by mucosal bleeding (39.5%). Severe bleeding was seen in 5% of the patients. None of them had intracranial hemorrhage. Twenty patients underwent splenectomy, and the rate of complete remission was 70%. Spontaneous complete remission was seen in 29% of the patients, and the median time to spontaneous complete remission was 3 years. Conclusions: Our study showed that almost one-third of patients with chronic ITP experienced spontaneous complete remission in an average of 3 years, and splenectomy provided satisfactory results in severe cases. This study demonstrates the natural history of chronic ITP in childhood before the era of eltrombopag.